Transaction Data Security Using AES and RC4 - Puji Sari Ramadhan; Muhammad Syahril; Rini Kustini; Hendryan Winata; Robin Darwis Gea (CESS (Journal of Computer Engineering, System and Science), 2023)
This study discusses the effectiveness of using AES (Advanced Encryption Standard) and RC4 (Rivest Chipper 4) as digital data security algorithms to prevent and protect transaction data from irresponsible parties. This needs to be done because the development of sales transactions or other services has used digital technology a lot. This situation causes the need to secure digital data from existing transactions, so that transaction data can be stored safely. Transaction data security is carried out by changing data into ciphers or codes that are difficult to read using the AES (Advanced Encryption Standard) and RC4 (Rivest Cipher 4) algorithms. This research begins by collecting existing transaction data and then transforming it into ASCII code. The results of the transformation will be used to perform calculations using the AES algorithm. After completing the calculation process using the AES algorithm, then do the calculations using RC4. These results will be stored in the database so that the transaction data that has turned into these codes cannot be known by other parties. The combination of the AES and RC4 algorithms is carried out to strengthen data encryption because there are more and more rotation systems and double security is carried out so that digital data is not easily read and misused. With the presence of this research, it can be shown that the AES and RC4 algorithms are capable of encrypting existing transaction data with multiple levels of security.